2010
DOI: 10.1016/j.cub.2010.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Stereotypical Cell Division Orientation Controls Neural Rod Midline Formation in Zebrafish

Abstract: The development of multicellular organisms is dependent on the tight coordination between tissue growth and morphogenesis. The stereotypical orientation of cell divisions has been proposed to be a fundamental mechanism by which proliferating and growing tissues take shape. However, the actual contribution of stereotypical division orientation (SDO) to tissue morphogenesis is unclear. In zebrafish, cell divisions with stereotypical orientation have been implicated in both body-axis elongation and neural rod for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
102
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(109 citation statements)
references
References 28 publications
7
102
0
Order By: Relevance
“…Divisions oriented preferentially to an elongating axis have the potential to facilitate polarized extension of that tissue. This mechanism has been reported for zebrafish gastrulation, for example (Gong, Mo, & Fraser, 2004; Quesada-Hernández et al, 2010). In chick primitive streak formation, cells divide at the midline to orient primitive streak development (Wei & Mikawa, 2000).…”
Section: Introductionsupporting
confidence: 64%
“…Divisions oriented preferentially to an elongating axis have the potential to facilitate polarized extension of that tissue. This mechanism has been reported for zebrafish gastrulation, for example (Gong, Mo, & Fraser, 2004; Quesada-Hernández et al, 2010). In chick primitive streak formation, cells divide at the midline to orient primitive streak development (Wei & Mikawa, 2000).…”
Section: Introductionsupporting
confidence: 64%
“…2B; perpendicular). Studies in zebrafish gastrulation have shown that cells in dorsal tissues preferentially divide along the animal-vegetal axis of the embryo (Gong et al, 2004) and may be coupled with cell rearrangements and cell shape changes to drive axis elongation (Quesada-Hernández et al, 2010). Within the chick primitive streak, oriented cell divisions play a role in streak elongation (Wei and Mikawa, 2000).…”
Section: Cranial Neural Crest Cell Proliferation Dynamicsmentioning
confidence: 99%
“…Genetic and fatemapping studies demonstrate the existence of a population of bipotential neural/mesodermal stem cells in the mouse and zebrafish tailbud (Martin and Kimelman, 2012;Takemoto et al, 2011;Tzouanacou et al, 2009). Inhibition of cell division during gastrulation and/or the segmentation period modestly reduces body length, suggesting that cell migration primarily drives elongation (Harrington et al, 2010;Quesada-Hernández et al, 2010;Zhang et al, 2008). In zebrafish, cell-labeling and cell-tracking experiments have elucidated the spatiotemporal patterns of cell movement and cell division in the blastula, gastrula and early tailbud (Kanki and Ho, 1997;Keller et al, 2008;Olivier et al, 2010).…”
Section: Introductionmentioning
confidence: 99%